The Integrated Human-Like Agent Model for Fear Dynamics of Persons With Post Traumatic Stress Disorder - Fadahl, Zaid Abass (2012)
Post-traumatic Stress Disorder (PTSD) is associated with impairments in emotional experience and expression. In most training environments for clinical psychology, a human agent model used to simulate the real world and to ensure full control of all the parameters implied during the experiments. This kind of model is expected to encapsulate a number of important patterns that related to the underlying theories of PTSD. Hence, it allows clinical psychologists to manipulate several important parameters and relate it to the important findings in their respective domains. Therefore, the outcome from this project is a human-agent model that generates related emotion displays (particularly sad and fear) of PTSD patient. A computational model is developed to simulate the purpose conditions. A number of experiments have been conducted to evaluate the proposed model.